Analysis of the Impact of D-PSM (Digital Public Service Mall) Innovation in Bangkalan on Enhancing Responsiveness, Neutrality, Accountability, & Legal Compliance as a Representation of NWS (Neo-Weberian State) - Windayati Windayati; Bintoro Wardiyanto; Erna Setijaningrum (Journal Research of Social Science, Economics, and Management, 2025)
This study analyzes the impact of the Digital Public Service Mall (Digital Public Service Mall/D-PSM) innovation implemented in Bangkalan Regency on improving the quality of public services, particularly in terms of responsiveness, neutrality, accountability, and legal compliance as core principles of the Neo-Weberian State (NWS). The D-PSM innovation was developed to modernize public service delivery through digitalization by integrating various administrative services from multiple agencies into a single, accessible, and efficient digital platform. This study employs a qualitative descriptive approach using secondary data sources, including official government reports, internal evaluation documents, policy regulations, and relevant academic literature. The findings indicate that D-PSM has significantly improved service accessibility, processing speed, and transparency, thereby reducing bureaucratic complexity and enhancing public trust. The implementation of digital systems has also strengthened accountability mechanisms through traceable service processes and standardized procedures. However, the study identifies persistent challenges, particularly related to limited internet connectivity, uneven digital literacy, and unequal access to services in remote and rural areas of Bangkalan Regency. Despite these constraints, official evaluations by the Ministry of Administrative and Bureaucratic Reform (Kemenpan-RB) categorize D-PSM Bangkalan as “active,” reflecting positive institutional performance. This study concludes that D-PSM represents a meaningful step toward NWS-oriented governance and recommends strengthening digital infrastructure, expanding technical capacity, and improving inclusivity to achieve a more responsive, neutral, and accountable public service system.